The evaluation of stakeholder maturity in the development of sustainable tourism - Almukhambetova В.; Baimbetova А.; Yrza, B. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2025)
Purpose of study - of this research is to identify the extent of which representatives in the tourism business, government authorities, public organizations, and the local population are aware of and interpret the principles of sustainable tourism, as well as determine the key factors influencing the effectiveness of their interaction. The methodology - of the study consists of semi-structured interviews with various stakeholder groups, content analysis of conveniently transcribed material and finally a comparison with benchmark-maturity models with these achieved findings. The findings of this research can be employed to draw up recommendations for politicians, local communities and businesses about how to improve the planning and implementation of environmental, socially responsible activities. As well as the respondents as a whole have only a fragmented, sometimes inconsistent grasp of sustainable development and there is little communication between groups. Comparison with benchmark maturity models revealed significant differences between the current and the required levels of interaction. Conclusion - improving stakeholder maturity has become a key requirement for forming a balanced strategy for sustainable tourism development. It is recommended to strengthen institutional coordination, expand educational programs, and implement mechanisms for systematic cooperation, which will help reinforce the competitiveness of the city of Turkestan.